2023
DOI: 10.1021/acs.orglett.3c00674
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Direct Cross-Coupling of Aryl Fluorosulfates with Aryl Bromides

Abstract: A one-pot, direct cross-coupling of aryl fluorosulfate with aryl bromide, which is step-economical and avoids the use of a preprepared/ commercial organometallic reagent, could be accomplished by performing the reaction in THF at room temperature in the presence of nickel catalyst, magnesium turnings, and lithium chloride, giving rise to the corresponding biaryls in moderate to good yields with reasonable functional group compatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In 2023, Shen's group [100] also proposed a novel method for the direct cross-coupling of aryl fluorosul-fates and aryl bromides with an economical catalyst Ni. Preliminary mechanistic studies indicated the possible reaction pathway that aryl bromides follow to transfer to Grignard reagent under the presence of magnesium turnings and then perform with aryl fluorosulfates (Scheme 38).…”
Section: Other Reactionsmentioning
confidence: 99%
“…In 2023, Shen's group [100] also proposed a novel method for the direct cross-coupling of aryl fluorosul-fates and aryl bromides with an economical catalyst Ni. Preliminary mechanistic studies indicated the possible reaction pathway that aryl bromides follow to transfer to Grignard reagent under the presence of magnesium turnings and then perform with aryl fluorosulfates (Scheme 38).…”
Section: Other Reactionsmentioning
confidence: 99%
“…Aryl fluorosulfates show excellent stability against hydrolysis and thermolysis when compared to sulfonyl halides . These advantages of aryl fluorosulfates have enabled their exploration as a convenient source of electrophiles within catalytic reactions. However, there is a lack of experimental characterization of well-defined nickel complexes within catalytic cycles. Herein, we present an efficient deoxygenative borylation of aryl fluorosulfates under mild conditions, achieved through nickel-catalyzed C–O bond activation instead of the typical S–F bond cleavage in SuFEx chemistry.…”
Section: Introductionmentioning
confidence: 99%